Sistem Informasi Geografis Pencarian Lokasi Kafe di Medan Menerapkan Algoritma Tabu Search (TS) - Julianti Julianti (STMIK Budi Darma, 2019)
The cafe business in Medan is currently growing very rapidly. This can be seen by the many cafes that have sprung up, because cafes have become a lifestyle for most people today. The existence of the location of cafes in the city of Medan very much and almost every city of Medan there are more than one cafe. Because the amount that spreads makes people confused even do not know the location of the location of the cafe. Requires a system to check the intended location. Based on these problems, the writer will discuss about making a Geographic Information System for Locating Cafe Locations in the City of Medan Using the Tabu Search Algorithm. This system is made using Android-based, where in this system there is location information, consisting of an address, as well as route routes that can be used to get to the location of the cafe. In this process only the admin can process input data, edit data and delete data. While users can only look for information on the location of cafes in the city of Medan. With a simple and easy-to-understand system for the public to access information on the search for cafe locations, it can be used as an effort to introduce technology based on geographic information systems to the public.